Modelo de gestão assistencial para a Rede EBSERH baseado na cogestão, núcleo interno de regulação, Kanban e painel de indicadores - Lang, Cláudia Emília (2018)
Introduction: Hospital management has been gaining more and more importance due to the expansion of health systems and the complexity of the organization of hospital services. However, throughout its history, Brazilian public hospitals, including university ones, were conducted to oppose a low qualified management, including in the area of care, where they work in an individualized manner, with little interaction among the professionals involved in patient care. In Brazil, university hospitals have a fundamental importance in the evolution of Health Unic System (SUS), as well as in the training of human resources active in professional practices, in the development of research and in the incorporation of new technologies for collective health. To improve the management of federal university hospitals, Ministry of Education (MEC) created the Brazilian Hospital Services Company (Ebserh), setting performance targets, deadlines and indicators, as well as investing in human resources, infrastructure and technology. Objectives: To present a proposal for intervention that consists of disseminating the step-by-step model of an Assistive Management model for the university hospitals that are part of the Ebserh network based on co-management and devices such as Kanban, NIR (Internal Regulation Nucleus) and Indicators panel. Materials and Methods: Applied research, qualitative, in a context of bibliographic review of the Narrative Review type, with intervention proposal. The population of the field research is the set of university hospitals of the Ebserh network, and the sample is the hospital of origin of the author, where these healthcare management devices have already been implanted. The population of the theoretical research was defined through the collection of data and was based on the research of bibliography on the selected themes and of experiences already experienced by other hospitals. Results: A total of 07 articles on hospital management, 23 articles and 03 books on the subject of co-management / participatory management, 07 articles on the use of the Kanban tool in a hospital environment, 11 articles on in-hospital bed regulation and 10 articles on hospital management were collected use of indicators in hospital management. Of these, 21 were selected for the basis of the intervention proposal. Product: Assistance Management Model to be implemented in university hospitals of the Ebserh Network, which will serve as an embryo for the development of an increasingly professional and qualified assistance. Conclusion: We observed the poor qualification of health care management in the Brazilian public service, reflected in the low number of publications on the subject, as well as the lack of training of healthcare workers on the management of their work processes. We conclude that the implementation of a Management Model for Ebserh University Hospitals, based on co-management and basic care management devices, would provide a qualification of assistance based on innovation and scientific evidence, bringing quality and efficiency, as well as providing a position among Brazilian public hospitals.